PENGARUH KUALITAS PRODUK DAN PERIKLANAN TERHADAP KEPUTUSAN PEMBELIAN BINGKAI FOTO PADA TOKO PASUNDAN GALLERY LUBUKLINGGAU - Ronal Aprianto (LPPM UNIVERSITAS BINA INSAN, 2017)
The purpose of this study is to find out the effect of product quality and advertising together on purchasing decisions. The sampling technique used in this study was accidental sampling technique. Data collection techniques using a questionnaire (questionnaire) that has been tested first using validity and reliability testing. The data analysis technique used is the classical assumption test (linearity test and normality test), multiple linear regression, coefficient of determination, and F test, where the researcher uses the help of SPSS version 20. The regression analysis results obtained the equation: Y = 0.960 + 0.582 X1; + 0.646 X2 which means that purchasing decisions are influenced by product quality and advertising. The results of the regression analysis also obtained a coefficient of determination (R2 = 0.474) or equal to (47.4%). This means that (47.4%) purchasing decision variables are influenced by product quality and advertising variables. The remaining (52.6%) is explained by other variables, such as consumer behavior, service, product quality service, product quality services, and customer satisfaction. The conclusion is that Product Quality and Advertising together have a significant effect on Photo Frame Purchase Decisions at the Pasundan Shop Gallery Lubuklinggau. This is evident from the results of the F test which obtained calculated as 75,477 received at the 15% significance level.